Exploration of fine art photography as a medium for self-expression / Andrialis Abdul Rahman and Nur Nafishah Azmi - Abdul Rahman, Andrialis; Azmi, Nur Nafishah (Faculty of Art and Design, 2024)
The purpose of this study is to investigate the ethics of fine art photography through the lens of self-expression. Specifically, the study focuses on privacy, permission, and the creative utilisation of human experiences. My ability to express myself through photography could be beneficial. Using both observation and case studies, we investigate how the influence of fine art photography on self-expression arises. People are able to visually represent their thoughts, feelings, and experiences through the medium of fine art photography, which also alters their self-expression and contributes to the process of self-discovery. Through the use of high art photography, this research evokes feelings and recollections. The composition, lighting, subject matter, and post-processing techniques all contribute to the creation of well-considered photos. Within the realm of fine art photography, this study promotes the exploration of self-expression through the creation of photographs that generate feelings, conversations, and identities.